Neutralization of Interleukin 1-beta is associated with preservation of thalamic capillaries after experimental traumatic brain injury - Özen, Ilknur; Clausen, Fredrik; Flygt, Johanna; Marklund, Niklas; Paul, Gesine (Frontiers in Neurology, 2024)
Introduction Traumatic brain injury to thalamo-cortical pathways is associated with posttraumatic morbidity. Diffuse mechanical forces to white matter tracts and deep grey matter regions induce an inflammatory response and vascular damage resulting in progressive neurodegeneration. Pro-inflammatory cytokines, including interleukin-1β (IL-1β), may contribute to the link between inflammation and the injured capillary network after TBI. This study investigates whether IL-1β is a key contributor to capillary alterations and changes in pericyte coverage in the thalamus and cortex after TBI. Methods Animals were subjected to central fluid percussion injury (cFPI), a model of TBI causing widespread axonal and vascular pathology, or sham injury and randomized to receive a neutralizing anti-IL-1β or a control, anti-cyclosporin A antibody, at 30 min post-injury. Capillary length and pericyte coverage of cortex and thalamus were analyzed by immunohistochemistry at 2- and 7-days post-injury. Results and Conclusion Our results show that early post-injury attenuation of IL-1β dependent inflammatory signaling prevents capillary damage by increasing pericyte coverage in the thalamus.